An SNMP filesystem in userspace - Lopes, Rui Pedro (2013)
Modern computer networks are constantly increasing in size and complexity. Despite this, data networks are a critical factor for the success of many organizations. Monitoring their health and operation sta- tus is fundamental, and usually performed through specific network man- agement architectures, developed and standardized in the last decades. On the other hand, file systems have become one of the best well known paradigms of human-computer interaction, and have been around since early days in the personal computer industry. In this paper we propose a file system interface to network management information, allowing users to open, edit and visualize network and systems operation information.